Analisis Kesalahan Berbahasa Tataran Fonologi dan Morfologi pada Teks Sinopsis Cerita Karya Siswa Kelas V SD Negeri Menuran 03 Sukoharjo (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
Language occupies a very crucial role for humans in this life, especially in terms of communication with other humans. One of the language skills used to communicate indirectly is writing skill. In the world of writing, writing mistakes have become a natural thing. Therefore, this study aims to improve and describe various errors in the Indonesian language at the phonological and morphological levels in the story synopsis text by students of class V SD Negeri Menuran 03. The method used in this study is a qualitative descriptive method. The data source in this study came from written data in the form of story synopsis text results, while the data collection technique used was reading and note-taking techniques. The results of this study indicated that there were 45 language errors at the phonological and morphological levels. At the phonological level (adding phonemes, changing phonemes, and removing phonemes) there were 30 errors or 66.7%, while at the morphological level (affixation and reduplication) there were 15 errors or 33.3%.